“GOODBYE GLOBALISATION: THE RETURN OF A DIVIDED WORLD” BY ELISABETH BRAW (Glocalism: Journal of Culture, Politics and Innovation, 2025)
Review of the book "Goodbye Globalisation: The Return of a Divided World" by Elisabeth Braw